2018
DOI: 10.1103/physrevb.98.045305
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of nanoscale Anderson localization induced by intrinsic compositional disorder in InGaN/GaN quantum wells by scanning tunneling luminescence spectroscopy

Abstract: We present direct experimental evidences of Anderson localization induced by the intrinsic alloy compositional disorder of InGaN/GaN quantum wells. Our approach relies on the measurement of the luminescence spectrum under local injection of electrons from a scanning tunneling microscope tip into a near-surface single quantum well. Fluctuations in the emission line shape are observed on a few-nanometer scale. Narrow emission peaks characteristic of single localized states are resolved. Calculations in the frame… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…The full width at half maximum (FWHM) of the (0006), (10)(11)(12)(13)(14)(15) and (-1015) reflexes were determined to be 282, 171 and 313 arcsec, respectively, confirming suitable crystal quality as already observed by STEM. Fully coherent growth of the entire epilayer stack was concluded from reciprocal space maps of asymmetric (10-15) and (-1015) reflexes.…”
Section: Xrdsupporting
confidence: 71%
“…The full width at half maximum (FWHM) of the (0006), (10)(11)(12)(13)(14)(15) and (-1015) reflexes were determined to be 282, 171 and 313 arcsec, respectively, confirming suitable crystal quality as already observed by STEM. Fully coherent growth of the entire epilayer stack was concluded from reciprocal space maps of asymmetric (10-15) and (-1015) reflexes.…”
Section: Xrdsupporting
confidence: 71%
“…Nevertheless, the Stokes shift as large as 20 meV at room temperature [17] indicates a strong lateral localization of the QW excitons. Origin and scale of the potential fluctuations in (In,Ga)N/GaN QWs were investigated by various methods, including transmission electron microscopy [5], near-field scanning optical microscopy [22], and scanning tunneling luminescence spectroscopy [23]. In particular, Hahn et al showed that micro-PL spectra display significant and chaotic potential variations on the scale of about 3 nm [23].…”
Section: Discussionmentioning
confidence: 99%
“…Origin and scale of the potential fluctuations in (In,Ga)N/GaN QWs were investigated by various methods, including transmission electron microscopy [5], near-field scanning optical microscopy [22], and scanning tunneling luminescence spectroscopy [23]. In particular, Hahn et al showed that micro-PL spectra display significant and chaotic potential variations on the scale of about 3 nm [23]. This is commensurable with the free exciton Bohr radius in GaN of about 3 nm [24] and might provide a reason for the modification of the T 1 time connected with the exciton oscillator strength.…”
Section: Discussionmentioning
confidence: 99%
“…As the scale of intrinsic disorder of alloys is a few nm (Figure 2b), it is not observed through these techniques. Only the recently developed technique of scanning tunneling luminescence (STL) provides spatial resolution at the few-nm scale and allows direct observation of localized states induced by the intrinsic disorder [19]. The indirect impact of nm-scale disorder can however be observed at the macroscopic level, through spatially averaged observations.…”
Section: Experimental Evidence Of Directly Observable Disorder-inducementioning
confidence: 99%
“…Such measurements are spatially averaged effects of interface disorder and one would wish more direct observations of the interface fluctuations. The STL technique provides spatial resolution at the few nm scale and could probe the interface morphology because of the very localized nature of the probing carrier density [19].…”
Section: Experimental Evidence Of Directly Observable Disorder-inducementioning
confidence: 99%